1987
DOI: 10.1164/arrd.1987.135.4.954
|View full text |Cite
|
Sign up to set email alerts
|

Functional Residual Capacity in Healthy Preschool Children Lying Supine1,2

Abstract: IntroductionDetermination of normal values for many aspects of lung function in preschool children is often difficult since they do not readily comprehend instructions for pulmonary function testing and can be uncooperative. One basic aspect of lung function that can be measured in anesthetized (1) and in awake cooperative preschool children (2) is FRC. Normal values have been derived for sitting and standing subjects (2-4). However, these studies may not be applicable to supine children, as the FRC is known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Therefore, in this study, lung volume was measured on the scans and this volume was related to the predicted values for FRC. The technique used to make the prediction equations is different for the children aged v6 yrs [10] compared to the older children [11]. BAR-YISHAY et al [10] measured FRC in the supine position, ZAPLETAL et al [11] measured FRC in the sitting position.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in this study, lung volume was measured on the scans and this volume was related to the predicted values for FRC. The technique used to make the prediction equations is different for the children aged v6 yrs [10] compared to the older children [11]. BAR-YISHAY et al [10] measured FRC in the supine position, ZAPLETAL et al [11] measured FRC in the sitting position.…”
Section: Discussionmentioning
confidence: 99%
“…The technique used to make the prediction equations is different for the children aged v6 yrs [10] compared to the older children [11]. BAR-YISHAY et al [10] measured FRC in the supine position, ZAPLETAL et al [11] measured FRC in the sitting position. This results in higher values for FRC in the older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FRC in children correlates well with height, weight, and age; but there is no difference in FRC between the sexes.4-6 The ratio of FRC to body weight increases with age. [4][5][6] reported that the ratio of FRC to body weight was 17 5:4 ml-kg -I in infants and 24 + 6 ml-kg -I in children more than one year of age. Oxygen consumption is relatively greater in younger than in older children.…”
Section: Discussionmentioning
confidence: 99%
“…The CT-determined gas volume was compared with predicted normal values for functional residual capacity and TLC using standard prediction equations based on body length [1,4,[43][44][45]. CT-calculated lung expansion was compared between males and females.…”
Section: ð1þmentioning
confidence: 99%